THE PROCESS OF HIGHER LEARNING IN SCHOOL PHYSICAL EDUCATION/ABSTRACT (Fiep Bulletin - online, 2011)
The teaching learning process in Physical Education is under discussion for a long time. This discussion is necessary in that other pedagogical approaches would allow physical education teachers able to reframe their practice teaching. This redefinition allows us to understand the student as knowing subject, autonomous, able to understand the nature of its expression. Thus the student becomes a constructor of knowledge rather than mere receiver of information, there is a relationship between educator and student, a social-historical perspective, so as to respect its context of insertion as well as their cultural interests and meanings. From this initial context, this study aimed at understanding the teaching learning process of Physical Education from the conceptions of historical and dialectical materialism. To this end we used a literature search, and the historical and dialectical materialism to the theoretical framework for analysis and discussion of results. The practice of teaching physical education is very important that developed from the importance of culture as an expression maximum body of embodiment, not only as a means of training. When offered in a reflective way becomes more meaningful and transformative. The Physical Education now has mainly develops in a policy and technicalities, not respecting the individuality of each student. An interdisciplinary perspective suggests a relationship between fields of knowledge, which acts as a negation of the other, thus bringing theory and practice and avoiding totalizing claim, but a significant pedagogical praxis properly. Keywords: Teaching Learning process; Physical Education; Praxis teaching.
Keywords: Teaching Learning process; Physical Education; Praxis teaching